Pengaruh Harga Dan Kualitas Produk Terhadap Keputusan Pembelian - Farah Salsabilla; Muhammad Iqbal Fasa (PT. Intelek Cendikiawan Nusantara, 2024)
This research aims to determine the influence of price and product quality on purchasing decisions. The approach taken is to use a descriptive approach to find out whether product price and quality influence consumer purchasing decisions. The method used in this research is qualitative by focusing on the discussion of previous research, both a collection of previous journals and library research to obtain research data results using the literature reviewresearch method. The research results state that the better the price set, the consumer purchasing decisions will increase and the better the product quality is determined, the consumer purchasing decisions will increase.